Experiences and effectiveness of occupational therapy interventions delivered in the acute setting: a mixed methods systematic review protocol. Issue 9 (7th September 2021) - George, Stacey; Barrett, Matt; De Ionno, Jessica; Fletcher, Laura; Choo, Wen Shin; Rivas-Dominguez, Sergio; Romanic, Nikolina; Lizarondo, Lucylynn; Stern, Cindy
ABSTRACT: Objective: The objective of this review is to synthesize and integrate the best available evidence on the experiences and effectiveness of occupational therapy interventions delivered in the acute setting. Introduction: Occupational therapy is a client-centered health profession promoting health and well-being through occupation. In acute hospital settings, occupational therapy interventions are provided to patients to maximize function, prevent readmission, and promote safe discharge. Recent studies have demonstrated that occupational therapy has modified its practice in acute settings to include advocacy, team facilitation, and rapid clinical reasoning. This review will investigate not only the effectiveness of occupational therapy interventions, but also the experiences of patients, caregivers, and clinicians in the acute setting. Inclusion criteria: This review will consider qualitative, quantitative, and mixed methods studies on the experiences and effectiveness of occupational therapy interventions delivered in acute settings. For the qualitative component, the experiences of patients and caregivers receiving any occupational therapy intervention, and clinicians directly or indirectly involved in delivering occupational therapy interventions, will be investigated. For the quantitative component, occupational therapy interventions will be compared with non-occupational therapy interventions, no intervention, wait-list, or other inactive or active (usual care) control interventions. Patient outcomes will include impairment, activities of daily living, psychological outcomes, and quality of life, while health system outcomes will include health care utilization and patient flow. Methods: The databases to be searched include CINAHL, Cochrane Controlled Trials Register, MEDLINE (Ovid), OT Seeker, PsycINFO (Ovid), and Scopus. Study selection, critical appraisal, data extraction, and data synthesis and integration will utilize the JBI segregated approach to mixed methods systematic reviews. Systematic review registration number: PROSPERO CRD42020206363